1977
DOI: 10.1097/00000658-197707000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tumors in Choledochal Cysts

Abstract: Between 1960 and 1975, 17 patients with congenital cystic dilatation of the common bile duct (choledochal cyst) were treated and three were associated with malignant tumors in the cysts and one was with carcinoma of the gallbladder. Preoperative diagnosis of adenocarcinoma in the choledochal cyst was established in one patient by cytologic examination of the bile which was obtained during the procedure of endoscopic pancreaticocholangraphy (EPCG) and percutaneous transhepatic cholangiography (PTC). Definitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 16 publications
2
41
0
2
Order By: Relevance
“…The incidence of malignancy ranges from 10% to 30%. [10][11][12][13][14][15] Complete cystic excision with hepaticoenterostomy is the standard surgical strategy because it lowers the risk of malignancy arising from the residual cyst. However, there is a lack of consensus about the optimal timing of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malignancy ranges from 10% to 30%. [10][11][12][13][14][15] Complete cystic excision with hepaticoenterostomy is the standard surgical strategy because it lowers the risk of malignancy arising from the residual cyst. However, there is a lack of consensus about the optimal timing of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder carcinoma is associated with AJPBD in approximately 10% of patients. In this regard, several investigations revealed that among AJPBD patients without a dilatation of common bile duct, the incidence of gallbladder carcinoma is higher than in those with choledochal cyst, a cystic dilatation of common bile duct [35,36,37].…”
Section: Anomalous Junction Of the Pancreaticobiliary Ductmentioning
confidence: 99%
“…Multiple factors such as mechanical irritation by calculi, bile stasis, and bacterial infection seem to be factors in the etiology of biliary carcinoma. A further specific and well-documented risk factor for biliary cancer is congenital choledochal cyst, which is almost always associated with the anomalous arrangement of the pancreatobiliary duct system [7, 8]. This anomaly allows reflux of pancreatic juice into the biliary tree.…”
Section: Discussionmentioning
confidence: 99%